IMPLEMENTASI MEDIA EPINTAR BERBASIS CULLTURALLY RESPONSIVE TEACHING UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS III PADA MATERI TANDA BACA DAN HURUF KAPITAL - Novia Anggraini, Asha; Farida Istianah; Ismawatin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research uses a type of classroom action research whose subject is carried out in class 3 of SD Labschool Unesa 1. This research uses qualitative data processing methods to describe the results of data calculations, and quantitative to analyze and calculate test data on learning outcomes and media validation. EPINTAR media validity results were obtained from media expert validation 92.30%. The implementation of cycles 1 and 2 experienced an increase in student learning outcomes which obtained a percentage of 11.11% with the criteria for cycle 1 obtaining 83.33% and cycle 2 obtaining 94.44%. This classroom action research is entitled "Implementation of E-Smart Media Based on Culturally Responsive Teaching to Improve Class III Student Learning Outcomes on Punctuation and Capital Letters".